A scoping review of recommendations in the English language on conducting research with trauma-exposed populations since publication of the Belmont report; thematic review of existing recommendations on research with trauma-exposed populations. - Kevin Jefferson; Kaitlyn K Stanhope; Carla Jones-Harrell; Aimée Vester; Emma Tyano; Casey D Xavier Hall (PLoS ONE)
Objective To identify recommendations for conducting public health research with trauma-exposed populations. Methods Researchers searched Embase, PubMed, Scopus, Web of Science, Open Grey, and Google Scholar for recommendations. Trauma that causes psychological impact was our exposure of interest and we excluded clinical articles on treating physical trauma. We reviewed titles and abstracts of 8,070 articles and full text of 300 articles. We analyzed recommendations with thematic analysis, generated questions from the existing pool of recommendations, and then summarized select gaps. Results We abstracted recommendations from 145 articles in five categories: community benefit, participant benefit, safety, researcher well-being, and recommendations for conduct of trauma research. Conclusions Gold standards to guide the conduct of trauma-informed public health research do not yet exist. The literature suggests participation in trauma research is not inherently harmful, and current recommendations concern using research to benefit communities and participants, protecting participants and researchers from harm, and improving professional practice. As public health researchers increasingly analyze trauma as a determinant of health, gold standards for the conduct of trauma-informed public health research would be appropriate and timely.